Plasmid Encoded Neurotoxin Genes in Clostridium botulinum Serotype A Subtypes - Marshall, Kristin M. (2007)
Clostridium botulinum, an important pathogen of humans and animals, produces botulinum neurotoxin (BoNT), the most poisonous toxin known. We have determined by pulsed-field gel electrophoresis (PFGE) and Southern hybridizations that the genes encoding BoNTs in strains Loch Maree (subtype A3) and 657Ba (type B and subtype A4) are located on large (~280 kb) plasmids. This is the first demonstration of plasmid-borne neurotoxin genes in Clostridium botulinum serotypes A and B. The finding of BoNT type A and B genes on extrachromosomal elements has important implications for the evolution of neurotoxigenicity in clostridia including the origin, expression, and lateral transfer of botulinum neurotoxin genes.